Visualizing the Knowledge Domain of Project Governance: A Scientometric Review - Zhao Zhai; Ming Shan; Amos Darko; Yun Le (Advances in Civil Engineering)
Over the past two decades, project governance has attracted increasing attention from researchers and practitioners worldwide and has become an important research area of project management. However, an inclusive quantitative and systematic analysis of the state-of-the-art recently available research in this field is still missing. This study attempts to map the global research on project governance through a state-of-the-art review. A total of 285 bibliographic records were retrieved from the Web of Science Core Collection database and analyzed by the visual analytic tool—CiteSpace. The results indicated that there has been an increasing research interest in project governance. The most productive and the most highly cited author in the area of project governance is Müller R., and most of the existing project governance research achievements are from Australia, China, USA, and Norway. By synthetically analyzing the keywords, future research might focus on governance of megaprojects and project success. Additionally, 9 knowledge domains of project governance were identified, including conceptual framework, public projects, governance structure, governance context, megaproject governance, contractual and relational governance, sustainability, portfolio governance, and project success. This study contributes to the body of knowledge by mapping the existing project governance research. It is particularly helpful to new and early-stage researchers who plan to do research on project governance, as it can provide them an overview of project governance research, including key authors, main institutions, hot topics, and knowledge domains. Moreover, the findings from the study are beneficial to industry practitioners as well, as they can help industry practitioners understand the latest development of governance theory and practice and thereby help them locate the best governance strategies for project management.